2011
DOI: 10.1088/0004-637x/730/1/52
|View full text |Cite
|
Sign up to set email alerts
|

A Stochastic Model for the Luminosity Fluctuations of Accreting Black Holes

Abstract: In this work, we have developed a new stochastic model for the fluctuations in light curves of accreting black holes. The model is based on a linear combination of stochastic processes and is also the solution to the linear diffusion equation perturbed by a spatially correlated noise field. This allows flexible modeling of the power spectral density (PSD), and we derive the likelihood function for the process, enabling one to estimate the parameters of the process, including break frequencies in the PSD. Our s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
211
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(218 citation statements)
references
References 136 publications
(210 reference statements)
7
211
0
Order By: Relevance
“…combinations of these datasets. The bend frequency estimate reported in the present paper is a factor ∼6 lower than that reported by McHardy et al (2007), but consistent with that from Kelly et al (2011). However, as discussed by McHardy et al (2007) the PSD of this source may be more complicated than the simple bending power law model assumes.…”
Section: Lack Of Qpossupporting
confidence: 87%
See 2 more Smart Citations
“…combinations of these datasets. The bend frequency estimate reported in the present paper is a factor ∼6 lower than that reported by McHardy et al (2007), but consistent with that from Kelly et al (2011). However, as discussed by McHardy et al (2007) the PSD of this source may be more complicated than the simple bending power law model assumes.…”
Section: Lack Of Qpossupporting
confidence: 87%
“…• Mrk 766: The PSD of Mrk 766 was studied by Vaughan & Fabian (2003), Markowitz et al (2007) and Kelly et al (2011). The main parameters (bend frequency and high frequency slope) are broadly compatible with our findings.…”
Section: Appendix A: Psd Breaks/bends In the Literaturesupporting
confidence: 84%
See 1 more Smart Citation
“…Due to the rather long time scales probed by BAT, the anticorrelations of variability with luminosity (Barr & Mushotzky 1986;Green et al 1993;Papadakis 2004) and with black hole mass (Papadakis & McHardy 1995;Zhou et al 2010;Kelly et al 2011Kelly et al , 2013Ponti et al 2012) often observed below 10 keV on short time scales are not detected in our hard X-ray study (Figs. 3 and 6).…”
Section: Long-term Variability Luminosity and Black Hole Massmentioning
confidence: 67%
“…This is a problem of importance not only in astrophysics but in many fields of physics, and various approaches towards a general explanation have been proposed (e.g., Press 1978;Pang et al 1995;Makse et al 1996). More recently, Kaulakys & Alaburda (2009) and Kelly et al (2011) proposed time series models based on superpositions of exponentially decaying outbursts occuring at random times and with random amplitudes. Both studies are able to reproduce the occurence of powerlaw power spectra.…”
Section: From Our Test We Can Draw Various Conclusionmentioning
confidence: 99%